Fibernamics Award Exhibition - Korae, Eva; Achilleos, Konstantina Niina; Vënëlainen, Tuomas (My University, 2025)
The research is based on Compo, a dough-like thermoplastic material historically used in mainland Europe to produce durable decorative elements for antique furniture. While its traditional production methods may appear unethical today due to the use of animal bones and rabbit skin, finished Compo objects can be safely disposed of as nutritious additions to household compost. The project tests the hypothesis that reintroducing pre-industrial techniques into contemporary manufacturing may help address problems of waste and overproduction, and is presented here through *The CompoStable Lamp*, an interpretation of the classic architect’s lamp made through mixing, kneading, turning, and rolling, alongside egg trays and 3D printing tests that demonstrate the material’s potential and the progress of the research.